KARAKTERISTIK LIMBAH BATANG SINGKONG SEBAGAI BIOMASSA CO-FIRING UNTUK PEMBANGKIT LISTRIK - Irawan, Dwi; Handono, Sulis Dri (TURBO [Tulisan Riset Berbasis Online], 2024)
This study evaluates the potential of wet cassava stems, dry cassava stems, and dry cassava stem powder as biomass fuels for co-firing in power plants. The analysis includes proximate testing, calorific value, and ultimate analysis to determine the quality and combustion efficiency of each material. Proximate test results show that dry cassava stems have lower moisture content and higher ash content compared to wet cassava stems, which can affect residue and slagging in power plant equipment. The high volatile matter content and significant increase in fixed carbon from wet to dry conditions indicate a greater extractable energy potential. The gross calorific value shows a significant increase from 2676.11 kcal/kg (AR) to 4929.44 kcal/kg (DAF) for wet cassava stems, and from 3910.64 kcal/kg (AR) to 5046.48 kcal/kg (DAF) for dry cassava stems. Dry cassava stem powder shows a very high calorific value, reaching 4272 kcal/kg (DB). The best ultimate analysis results for cassava stem powder are carbon (C) 48.44%, hydrogen (H) 6.61%, oxygen (O) 43%, sulfur (S) 0.15%, and nitrogen (N) 1.80%.